Psychometric properties of the Brazilian version of the Wound Quality of Life questionnaire - Tatiele Naiara Vogt; Pamella Naiana Dias Santos; Maria de Fátima Mantovani; Dabna Hellen Tomim; Paulo Ricardo Bittencourt Guimarães; Luciana Puchalski Kalinke (Universidade Federal do Ceará, 2020)
Objective: to evaluate the criterion validity and reliability of the Portuguese-Brazilian version of the Wound Quality of Life. Methods: methodological research with 100 participants. For criterion and reliability validation, the items in the Wound Quality of Life questionnaires were correlated with the Freiburg Life Quality Assessment Wound - Wound Version, using the Spearman correlation test and Cronbach's alpha. Results: the validity of concurrent criteria had a strong magnitude (0.85) when correlated with the Freiburg Life Quality Assessment Wound; the internal consistency had a Cronbach's alpha of 0.84. Conclusion: the validated questionnaire has good psychometric properties, is brief, easy to apply and reliable for assessing the quality of life of patients with wounds that are difficult to heal.